Cyclic plastic deformation mechanism and cyclic hardening model of Sanicro 25 steel welded joint - Li, Haizhou; Chen, Jintao; Chen, Hui; Xu, Lianyong; Wang, Qingyuan (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2021)
The low cycle fatigue (LCF) behaviors of Sanicro 25 steel welded joint were investigated under different total strain amplitudes (Δεt/2) at 700 °C. The results revealed that the stress amplitude increased with an increase in Δεt/2, while the fatigue life decreased. In addition, the cyclic hardening ratio first increased and then decreased with increasing Δεt/2. This abnormal trend was attributed to the variation in the cyclic yielding stress, indicating the evolution of the dislocation morphology. The microstructure analysis revealed a significant change in the cyclic plastic deformation mechanism from the dislocation tangle (0.2%–0.4%) to the entanglement of dislocations on the precipitate (0.5%) with an increase in Δεt/2. Furthermore, the cyclic hardening models considering the entanglement of dislocations on the precipitate and the dislocation tangle were unified according to the modified Taylor stress. The validated results indicated that the unified cyclic hardening model accurately calculated the maximum cyclic stress during LCF for a 316H welded joint.